2014
DOI: 10.3138/cjhs.2378
|View full text |Cite
|
Sign up to set email alerts
|

Somewhere under the rainbow: Exploring the identities and experiences of trans persons

Abstract: The literature on transgender/transsexual-spectrum persons is limited. Most studies are based on the assumption that trans persons are best understood within rigid and binary definitions of gender and sexuality and tend to focus on diagnostics, medical management and risk factors. Researchers and clinicians may also assume that people who challenge cultural norms of gender and sexuality can be grouped together. Such assumptions about the specific experiences of trans persons can be harmfully incorrect. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 41 publications
3
33
0
6
Order By: Relevance
“…As transgender individuals have been found to perpetuate traditional gender roles, this is not entirely surprising. For example, Dargie et al (2014) found that transgender women identified strongly with traditional feminine gender norms, while transgender men did the same with traditional masculine gender norms. Thus, rather than break down the gender binary, some transgender individuals may simply serve to reinforce conventional ideas about what it means to be a man or a woman.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As transgender individuals have been found to perpetuate traditional gender roles, this is not entirely surprising. For example, Dargie et al (2014) found that transgender women identified strongly with traditional feminine gender norms, while transgender men did the same with traditional masculine gender norms. Thus, rather than break down the gender binary, some transgender individuals may simply serve to reinforce conventional ideas about what it means to be a man or a woman.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that transgender persons have lower levels of social support (Dargie et al, 2014), which may indicate that they must become creative with the ways in which they find support. The Internet seems to be one such way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans-identities can also oppose the societal pressure of having to assign oneself to a clearly-delineated, distinct sex or gender at all; one might, instead, perceive oneself as being "somewhere in between" (e.g. as genderqueer, intergendered, multigendered, or gender fluid), or one might deliberately opt to elude gender or sex classification at all (Kuper et al 2012;Dargie et al 2014). …”
Section: Trans-identitiesmentioning
confidence: 99%
“…The transgender and gender non-conforming population belongs to "at-risk population" (Bostwick et al, 2010;Dargie et al, 2014;Craig et al, 2014;Singh & Burnes, 2009;Levitt & Ippolito, 2014;Mitchell et al, 2014;Meier et al, 2012;Zucker, Wood, Singh, & Bradley, 2012;Rothblum et al, 2013;Mathy, 2002;Pitts, Couch, Mulcare, Croy, & Mitchell, 2009). Standards of Care for the Health of Transsexual, Transgender, and Gender-Nonconforming People (herein after referred as SOC) mention also a higher prevalence of autism spectrum disorders in this population (Coleman et al, 2011).…”
mentioning
confidence: 99%